The prevalence of mental health problems among users of NHS stop smoking services: effects of implementing a routine screening procedure - Ratschen Elena; Todd Chloe; McNally Lisa (BMC, 2011)
Abstract Background Tobacco dependence among people with mental health problems is an issue that deserves attention both from a clinical and from a public health perspective. Research suggests that Stop Smoking Services often fail to ask clients about underlying mental health problems and thus fail to put in place the treatment adaptations and liaison procedures often required to meet the needs of clients with a mental health condition who want to stop smoking. This study assesses the recording of mental health problems in a large NHS stop smoking service in England and examines the effect of implementing a short screening procedure on recording mental health conditions. Methods Treatment records from the Stop Smoking Service covering a period of 13 months were audited. The prevalence of reported mental health problems in the six month period before the implementation of the mental health screening procedure was compared with that of the six month period following implementation. The screening procedure was only implemented in the support services directly provided by the Stop Smoking Service. Comparisons were also made with third-party sections of the service where no such screening procedure was introduced. Results The prevalence of reported mental health problems among a total of n = 4999 clients rose from less than 1% before implementation of the screening procedure to nearly 12% in the period following implementation, with the change being statistically significant. No significant rise was observed over the same period in the sections of the service where no screening procedure was implemented. Conclusions The absence of standard procedures to record mental health problems among service users in many stop smoking services is currently likely to prevent the detection of co morbidity. Implementing a simple screening procedure appears suitable to increase the routine recording of mental health problems in a stop smoking service, which is an essential step to ensure services can be tailored and delivered appropriately to the client group.